Implementation of E-Prokesmas Information Systems on Community Health monitoring in Jembrana Regency, Bali - Nugroho, J W J; Swastika, I P A; Daniaty, T O W (KnE Social Sciences, 2018)
Puskesmas (Community Health Center) have an important role in the society of Indonesia, especially in the current government. The Government of the Republic of Indonesia, through the Minister of Health of Indonesia announced the Healthy Indonesia Program, which is run on the basis of ministerial regulation, Guidelines For The Program Of Healthy Indonesian Programs with Family Approach, and in the Ministerial Regulation states that Implementation of Healthy Indonesia Program with Family Approach implemented by Puskesmas. For effectiveness of the program above, then E-Prokesmas Information System was built to be a tool of Puskesmas in monitoring the achievement of healthy family in its working area according to health indicators as government requirenments. The data displayed in E-Prokesmas is Web based GIS, that can display the health level status of the community such as percentage of healthy population, number of pre-healthy percentage and number of newborn mothers. Data collected above can be source of information for officer action in conducting health monitoring of sick members in the community.